Water Quality Monitor in Fish Ponds by using Wireless Sensor Networks (International Journal For Innovative Engineering and Management Research, 2020)
In fish ponds, the quality of water must be monitoring with the help of Wireless sensor networks. In this work, for water quality monitoring in aquaculture tanks to design set of sensors. The Wireless sensor network is based on substantial sensors, tranquil of trouble-free electronic machinery. The anticipated structure can supervise water quality in accumulation that the system includes a neat algorithm to condense the power dispel when transport the information from the node to the directory. The arrangement is together of three nodes in each tank that drive the information though the local area network to a database on the internet and a efficient algorithm that detects asymmetrical values and sends sound the alarm whereas they obtain position. All the sensors are premeditated and assemble to guarantee its appropriateness